Experimental Investigation on the Mechanical Properties of Concrete with Partial Replacement of Cement and Sand by Waste Marble Powder - U, Rajesh; Reddy, B. Sudharshan (Journal of Neonatal Surgery, 2025)
This study explores the mechanical performance of concrete incorporating waste marble powder (MP) as a partial replacement for both cement and sand. Four replacement levels—5%, 10%, 15%, and 20%—were evaluated across varying cement-to-sand substitution ratios (C:S = 0:100 to 100:0). The experimental program included compressive strength, split tensile strength, and flexural strength tests conducted at different curing ages. Results indicate that mixes with 10% (C50:S50) and 15% (C75:S25) MP replacement demonstrated the most favorable mechanical behavior, with notable improvements in strength and durability. Mix MP5 (C0:S100) exhibited high early-age strength, suggesting potential for rapid-setting applications. However, higher replacement levels (20%) led to reduced long-term strength and instability in the mix. Statistical validation using ANOVA confirmed the consistency of results across samples. The findings affirm the feasibility of using MP as a sustainable supplementary material in concrete, promoting environmental benefits by reducing industrial waste and reliance on natural construction materials.